Penerapan Total Productive Maintenance (TPM) Menggunkan Metode Overall Equipment Effectiveness (OEE) pada Kinerja Mesin Thermofix - Fauzia, Salsa Billa; Hendrawan, Aloysius Tommy; Khoiri, Halwa Annisa (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The PT. XYZ is a manufacturing company engaged in the textile industry. In recent years, there have been issues with production smoothness, one of which is the thermoflux machine frequently experiencing downtime, disrupting production flow. This research aims to analyse the Overall Equipment Effectiveness (OEE) value, identify loss factors based on the Six Big Losses, and identify the root causes of the problems. Based on the analysis conducted, an Availability Rate of 57% was obtained, a Performance Rate of 61.18%, a Quality Rate of 89.57%, and an OEE value of 30.68%. From the Six Big Losses identification results, the highest type of loss obtained is Reduce Speed Losses. Proposals for improving Autonomous Maintenance include daily checklists and routine cleaning. Planned Maintenance involves a maintenance schedule twice a month and monitoring runtime. Quality Maintenance adjusts machine parameters to meet standards. Focused Improvement is carried out through evaluations and inspection checksheets. Training and Education include monthly training, while Safety, Health and Environment ensures the use of PPE in accordance with SOP.. Keywords: Overall Equipment Effectiveness (OEE), Six Big Losses, Thermofix Machine, Total Productive Maintenance (TPM).